MiR-19a-3p containing exosomes improve function of ischaemic myocardium upon shock wave therapy. Issue 6 (13th August 2019) - Gollmann-Tepeköylü, Can; Pölzl, Leo; Graber, Michael; Hirsch, Jakob; Nägele, Felix; Lobenwein, Daniela; Hess, Michael W; Blumer, Michael J; Kirchmair, Elke; Zipperle, Johannes; Hromada, Carina; Mühleder, Severin; et al.
Abstract: Aims: As many current approaches for heart regeneration exert unfavourable side effects, the induction of endogenous repair mechanisms in ischaemic heart disease is of particular interest. Recently, exosomes carrying angiogenic miRNAs have been described to improve heart function. However, it remains challenging to stimulate specific release of reparative exosomes in ischaemic myocardium. In the present study, we sought to test the hypothesis that the physical stimulus of shock wave therapy (SWT) causes the release of exosomes. We aimed to substantiate the pro-angiogenic impact of the released factors, to identify the nature of their cargo, and to test their efficacy in vivo supporting regeneration and recovery after myocardial ischaemia. Methods and results: Mechanical stimulation of ischaemic muscle via SWT caused extracellular vesicle (EV) release from endothelial cells both in vitro and in vivo . Characterization of EVs via electron microscopy, nanoparticle tracking analysis and flow cytometry revealed specific exosome morphology and size with the presence of exosome markers CD9, CD81, and CD63. Exosomes exhibited angiogenic properties activating protein kinase b (Akt) and extracellular-signal regulated kinase (ERK) resulting in enhanced endothelial tube formation and proliferation. A miRNA array and transcriptome analysis via next-generation sequencing were performed to specify exosome content. miR-19a-3p was identified as responsible cargo, antimir-19a-3p antagonized angiogenic exosome effects. Exosomes and target miRNA were injected intramyocardially in mice after left anterior descending artery ligation. Exosomes resulted in improved vascularization, decreased myocardial fibrosis, and increased left ventricular ejection fraction as shown by transthoracic echocardiography. Conclusion: The mechanical stimulus of SWT causes release of angiogenic exosomes. miR-19a-3p is the vesicular cargo responsible for the observed effects. Released exosomes induce angiogenesis, decrease myocardial fibrosis, and improve left ventricular function after myocardial ischaemia. Exosome release via SWT could develop an innovative approach for the regeneration of ischaemic myocardium. Graphical Abstract: